PENINGKATAN AKTIVITAS DAN PRESTASI BELAJAR AL-QURAN HADIS MELALUI MODEL PEMBELAJARAN ATI (APTITUDE TREATMENT INTERACTION) PADA KELAS VIII 1&2 MTsN 10 TANAH DATAR TAHUN PELAJARAN 2019/2020 - M Misra (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Learning outcomes are essentially implied in learning objectives. Learning outcomes in madrasas are influenced by the capacity and quality of learning. The quality of learning is closely related to the availability of learning tools, learning models, interests of students and others. Through the existing learning tools, the selection of an appropriate learning model, it is hoped that the educational objectives will be achieved, namely the quality of learning which includes activities and student learning outcomes. Learning achievement is the skills and mastery of subjects, where mastery of these subjects is valued by numbers as a symbol of student achievement in learning. Learning achievement will increase if during the learning process activities of students always get attention.One alternative to improving the quality of learning is the application of learning models that pay attention to the different levels of individual abilities of students. The learning model that is able to appreciate the individual abilities of students is the ATI (Aptitude Treatment Interaction) learning model. ATI is expected to be able to answer the problem of the low activity and student achievement.This research is focused on the application of the ATI learning model in the learning of al-Quran Hadith in MTsN 10 Tanah Datar academic year 2019/2020. By taking research subjects in class VIII 1 and 2, because this class has serious problems, namely the low activity and learning achievement of the Koran.The method used in data collection is the method of observation and tests. While the analysis technique used is descriptive statistical techniques and quantitative analysis.The results showed that the ATI model was able to answer the problems raised, namely the low activity and learning achievement of the Koran of Hadith of students. From the two cycles set, it proves that the percentage of students' learning activities in cycles I and II, respectively: 78% and 88%. While the percentage of learning achievement of al-Quran Hadith in the first cycle and second cycle are 83% and 98%.